Cell cycle tracking for irradiated and unirradiated bystander cells in a single colony with exposure to a soft X-ray microbeam. (1st November 2016) - Kaminaga, Kiichi; Noguchi, Miho; Narita, Ayumi; Hattori, Yuya; Usami, Noriko; Yokoya, Akinari
Abstract: Purpose: To establish a new experimental technique to explore the photoelectric and subsequent Auger effects on the cell cycles of soft X-ray microbeam-irradiated cells and unirradiated bystander cells in a single colony. Materials and methods: Several cells located in the center of a microcolony of HeLa-Fucci cells consisting of 20–80 cells were irradiated with soft X-ray (5.35 keV) microbeam using synchrotron radiation as a light source. All cells in the colony were tracked for 72 h by time-lapse microscopy imaging. Cell cycle progression, division, and death of each cell in the movies obtained were analyzed by pedigree assay. The number of cell divisions in the microcolony was also determined. Results: The fates of these cells were clarified by tracking both irradiated and unirradiated bystander cells. Irradiated cells showed significant cell cycle retardation, explosive cell death, or cell fusion after a few divisions. These serious effects were also observed in 15 and 26% of the bystander cells for 10 and 20 Gy irradiation, respectively, and frequently appeared in at least two daughter or granddaughter cells from a single-parent cell. Conclusions: We successfully tracked the fates of microbeam-irradiated cells and unirradiated bystander cells with live cell recordings, which have revealed the dynamics of soft X-ray irradiated and unirradiated bystander cells for the first time. Notably, cell deaths or cell cycle arrests frequently arose in closely related cells. These details would not have been revealed by a conventional immunostaining imaging method. Our approach promises to reveal the dynamic cellular effects of soft X-ray microbeam irradiation and subsequent Auger processes from various endpoints in future studies.